Processing Instruction: An Input Based Approach for Teaching Grammar - Neupane, Madhu (Journal of NELTA, 2010)
The present article is an attempt to highlight the importance of teaching grammar in Second Language Acquisition (SLA). It outlines the arguments forwarded for and against teaching grammar and approaches to teaching grammar. Mainly the article focuses on Processing Instruction-an input based approach for teaching grammar. It also presents the methodology followed by its originators to provide the researchers who want to conduct a similar research. Key words: Second Language Acquisition, Processing instruction, input, output DOI: 10.3126/nelta.v14i1.3097 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 111-118